Sistem Informasi Geografis Pemetaan Perkebunan Sawit Berbasis Web - Zulafwan - (RJOCS (Riau Journal of Computer Science), 2016)
This written is examine about application web based geographical information system for Palm Plantation in West Pasaman regency. Geographical Information System (GIS) is a computer based system that can be use to find location on earth. Hopefully with this system will give information about Plam Plantaion in West Pasaman regency to all peoples. To build this system there are several steps. Beginning with data collection followed by phase of designthe user interface, make the programs, and the last is testing and implementation. On build this system some software is used like MapInfo Professional 10.5 to create the map and MapServerto run the web and mapfile.